Desert Plants Biology and Biotechnology - Ramawat, Kishan Gopal (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Deserts appear very fascinating during our short visits. However, the lives of plants and animals are very dif?cult under the harsh climatic conditions of high tempe- ture and scant water supply in deserts, sometimes associated with high concent- tions of salt. The editor of this book was born and brought up in the Great Indian Desert, and has spent much of his life studying the growth and metabolism of desert plants. It is very charming on a cool summer evening to sit at the top of a sand dune listening only to blowing air and nothing else. It has been my dream to prepare a volume on desert plants encompassing various aspects of desert plant biology. In this book, I have tried to present functional and useful aspects of the vegetation resources of deserts along with scienti?c input aimed at understanding and impr- ing the utility of these plants. The scant vegetation of deserts supports animal life and provides many useful medicines, timber and fuel wood for humans. Therefore, there are chapters devoted to medicinal plants (Chap. 1), halophytes (Chaps. 13, 14), and fruit plants (Chaps. 17, 20). Desert plants have a unique reproductive biology (Chaps. 9-11), well-adapted eco-physiological and anatomical charact- istics (Chap. 7), and specialised metabolism and survival abilities. These plants are dif?cult to propagate and pose many problems to researchers developing biote- nological approaches for their amelioration (Chaps. 18-20).